Atividades pedagógicas: relato de experiência em ambientes não escolares - HENCHEN, Eliane (2022)
In this study, my general objective was to report my experience in the Supervised Internship in Non-School Environments, carried out at the Psychosocial Care Center II (CAPS II), in the city of Altamira - Pará. Pedagogy, offered by the Faculty of Education (FAE), Federal University of Pará (UFPA), Altamira University Campus. In line with the general objective, the following specific objectives were defined: to understand how the pedagogue works in non-school environments; to discuss the importance of the supervised internship in the initial formation of the pedagogue; and report the execution of the intervention project carried out during the internship. This qualitative work was methodologically guided by action research, due to the particularities and functions of the institution in which it took place and the need to develop a pedagogical intervention project to comply with the Regulation that governs the internship activity. In this sense, considering the pre-established guidelines in the Regulation and, mainly, taking into account the experiences and experiences during the internship, I conclude that the curricular activities of Supervised Internship constitute not only spaces in which students relate theory-practice, but It is also a space for reflection on what education is – understood here as more than the teaching-learning processes that take place within formal teaching institutions – and on what social role the pedagogue will play in the future.